Recent advances in two-dimensional materials as catalysts for the electrochemical reduction of carbon dioxide - Xuanhao Mei; Weilin Xu (iScience, 2023)
Summary: Electrocatalytic carbon dioxide reduction reaction (CO2RR) is a newly developed strategy for energy conversion and carbon neutrality, which can achieve both valuable fuel generation and sustainable carbon cycles. Constructing well-defined, two-dimensional (2D) materials with abundant active sites and significant tunability is suitable for catalyst selections for the CO2RR. In this review, we first briefly introduce the fundamental information of the CO2RR and 2D materials. Then, the advantages of different types of 2D catalysts for electrocatalytic conversion of CO2 into value-added chemicals and fuels were emphasized. After that, several emerging strategies for tailoring 2D materials to enhance electrocatalytic performance were discussed and summarized systemically. Finally, the remaining challenges and prospects were also presented with optimization proposals for the possible applications of 2D materials as highly efficient nanoelectrocatalysts for CO2RR in the future.